2017
DOI: 10.1109/tdei.2017.006865
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electrical tree inception in silicone gels

Abstract: This work assesses the initial and crucial part of electrical treeing degradation, the inception stage, focusing on its dependence on applied voltage waveform and frequency. Tests have been performed on needle-plane configuration samples in solids and gels. A physical model has been formulated through an adaptation of an established theory for solids in which electrical tree inception is related to damage-producing injection currents. The voltage rise time appeared to be the most important parameter influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Due to the flexible polymer network chains as explained above, silicone gel possesses a unique two-phase liquid-solid nature, which makes the tree morphologies in silicone gel very different from solid materials. It was shown that under AC voltage, there is a filamentary branched component of trees in silicone gel that is retained after the electrical field is removed, like in solids, as well as bubble-like cavities that expand, become isolated, and collapse during growth, like streamers in liquid [8,15].…”
Section: Morphologies Of Electrical Treeing In Silicone Gelmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the flexible polymer network chains as explained above, silicone gel possesses a unique two-phase liquid-solid nature, which makes the tree morphologies in silicone gel very different from solid materials. It was shown that under AC voltage, there is a filamentary branched component of trees in silicone gel that is retained after the electrical field is removed, like in solids, as well as bubble-like cavities that expand, become isolated, and collapse during growth, like streamers in liquid [8,15].…”
Section: Morphologies Of Electrical Treeing In Silicone Gelmentioning
confidence: 99%
“…Electrical tree initiation in silicone gel for sinusoidal and square voltages as a function of the frequency applied was studied in [15]. It was found that a square waveform exhibits a much lower tree inception voltage (TIV) than a sinusoidal waveform at the low frequency of 1 Hz.…”
Section: (B) Effect Of Voltage Waveform and Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Step 4: Step 1 to Step 3 were repeated, incrementing the value of r by 0.1 nm, until calculated conductivity matches well with measured conductivity. The range of β was chosen from 10 −9 to 10 −7 according to [29]. Figure 5 shows a comparison of observed conductivity and calculated conductivity for x 10 oil-pressboard specimens having different ageing status.…”
Section: Hopping Conduction Modelmentioning
confidence: 99%
“…However, from the insulation side, frequency and slew rate are two of the most critical factors of a voltage pulse, which influences the level of degradation of the insulation systems that are exposed to such voltage pulses [4]. Solid dielectrics are found to be vulnerable to frequency, while the dominant factor for PD inception in liquid dielectrics is rising [5,6]. In this regard, the study of the insulation degradation of silicone gel, which has the properties of both liquids and solids can be challenging.…”
Section: Introductionmentioning
confidence: 99%